A Low-Cost, Point-of-Care Test for Confirmation of Nasogastric Tube Placement via Magnetic Field Tracking - Muneaki Miyasaka; Hao Li; Kon Voi Tay; Soo Jay Phee (Sensors, 2021)
In this work, we aim to achieve low-cost real-time tracking for nasogastric tube (NGT) insertion by using a tracking method based on two magnetic sensors. Currently, some electromagnetic (EM) tracking systems used to detect the misinsertion of the NGT are commercially available. While the EM tracking systems can be advantageous over the other conventional methods to confirm the NGT position, their high costs are a factor hindering such systems from wider acceptance in the clinical community. In our approach, a pair of magnetic sensors are used to estimate the location of a permanent magnet embedded at the tip of the NGT. As the cost of the magnet and magnetic sensors is low, the total cost of the system can be less than one-tenth of that of the EM tracking systems. The experimental results exhibited that tracking can be achieved with a root mean square error (RMSE) of 2–5 mm and indicated a great potential for use as a point-of-care test for NGT insertion, to avoid misplacement into the lung and ensure correct placement in the stomach.